Back to Back Modular Multilevel Converter with Dynamic Hybrid Link for High Performance Drive - Lillo-Cartes, J (IEEE Computer Society, 2021)
Back-To-Back Modular Multilevel Converter (BTB MMC) was proposed as an attractive alternative for medium-voltage drive application to decrease the inherent problem of high floating capacitor voltage fluctuations produced at low frequency machine operation. Recently the variation of DC-Link reference between the MMC and a control strategy based in control the machine side MMC as a current source was introduced to decrease the mitigation variables using during low frequency operation. However, it does not solve the problem to obtain the minimal capacitor voltage fluctuation during the entire machine operation. This paper propose a new method to obtain the minimum capacitor voltage fluctuation of the MMC modules during the entire machine operation range including an additional AC signal between the system common link. The proposed control strategy and overall performance of the system are verified by computational simulation. © 2021 IEEE.